Fluid and electrolyte balance considerations for female athletes. - Rodriguez-Giustiniani, P.; Rodriguez-Sanchez, N.; Galloway, S. D. R. (European Journal of Sport Science, 2022)
This review explores the effects of oestrogen and progesterone fluctuations across the menstrual cycle on fluid and electrolyte balance. The review aims to provide information on this topic for the exercising female but also for researchers working in this field. Beginning with a basic introduction to fluid and electrolyte balance, the review goes on to describe how oestrogen and progesterone have independent and integrated roles to play in the regulation of fluid and electrolyte balance. Despite evidence that oestrogen can influence the osmotic threshold for arginine vasopressin release, and that progesterone can influence aldosterone production, these actions do not appear to influence fluid retention, plasma volume changes at rest and during exercise, or electrolyte losses. However, the large inter-individual variations in hormonal fluctuations throughout the menstrual cycle may mean that specific individuals with high fluctuations could experience disturbances in their fluid and electrolyte balance. During phases of oestrogen dominance (e.g., late-follicular phase) heat dissipation is promoted, while progesterone dominance (e.g., mid-luteal phase) promotes heat conservation with overall higher basal body temperature. However, these responses do not consistently lead to any change in observed sweat rates, heat-stress, or dehydration. Finally, the literature does not support any difference in fluid retention during post-exercise rehydration periods conducted at different menstrual cycle phases. Although these mean responses largely reveal no effects on fluid and electrolyte balance, further research is required particularly in those individuals who experience high hormonal fluctuations, and greater exploration of oestrogen to progesterone interactions is warranted.